Practice-Based Simulation Model (PBSM) and Demonstration: Comparison of Critical Thinking of Nursing Students in Clinical Skill of Diabetic Wound Care - Issroviatiningrum, Retno; Amal, Ahmad Ikhlasul (International Journal of Psychosocial Rehabilitation, 2020)
Nurses must have critical thinking to provide good nursing care. Nursing education is important to support the student in achieving critical thinking skills to be a professional nurse. Learning methods that can be applied in laboratories to minimize undesirable events in hospitals and encourage students to think critically in making decisions are simulations and demonstrations. The purpose of this study was to determine the differences in practice-based simulation models and demonstrations of students’ critical thinking in conducting diabetic wound care clinical skills. This research method uses a quasi-experimental design. Sampling with a purposive sampling technique with a sample of 42 respondents. Students are given a simulation method with three stages, namely briefing, conducting simulation, debriefing, while, for demonstration of the stage of material exposure, demonstration, and remonstration. Students given the practice-based simulation model have critical thinking with a mean of 54.43 and a demonstration with a mean of 42.62. The independent t-test found that the p-value is 0.000. There was a significant difference in students’ critical thinking skills in performing diabetic wound care skills between the two groups. Students with simulation methods have a higher mean value compared to demonstrations. So students can apply the practice based simulation model as an innovative learning method in the laboratory to improve critical thinking if confronted with a case using simulated patients.